Visual Dashboard Program Penjualan pada Usaha Kecil Menengah (UKM ) Mutiara Surakarta dengan Visual Basic dan Crystal Report - Didik Warasto; Martono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
This paper discusses improving the sales system that has been used by UKM Mutiara Surakarta. Using the field study method. The field study is carried out by researching the company directly. This is done to obtain data and information directly with the problem under study. The field study is carried out by studying the information system developed by UKM Mutiara, as well as collecting data about information systems implemented by UKM UKM. The result is an inventory program designed using Visual Basic 6.0. With the creation of this program, the processing of inventory information systems implemented by UKM Mutiara Surakarta can be faster, more accurate, easier and obtain updates, especially in the inventory system.